Evaluation of the Efficacy of Topical Tetracycline in Enhancing the Effect of Narrow Band UVB against Vitiligo: A Double-Blind, Randomized, Placebo-Controlled Clinical Trial. (9th February 2014) - Kalafi, Amir; Jowkar, Farideh
Abstract : Background . Vitiligo is a pigmentary disorder characterized by depigmented macules due to absence of melanocytes. Increased levels of tumor necrosis factor alpha and interleukin-1 in the epidermis of lesions may play a role in keratinocyte apoptosis and less production of melanogenic cytokines. Tetracyclines reduce production of tumor necrosis factor alpha and interleukin-1. Objective . To evaluate the effect of topical tetracycline on vitiligo patients on phototherapy. Methods . Thirty cases of generalized stable vitiligo were chosen randomly and pigmentation of two assigned lesions on right and left sides (same size and location) was determined by vitiligo area severity index, and medication and placebo were randomly assigned to be applied twice daily on either right or left side, respectively. Images were taken of the lesions at the end of the 4th, 8th, and 12th weeks and pigmentations were compared to baseline using aforementioned index. The patients also took narrow band ultraviolet B two to three times a week. Results . Mean pigmentation, based on vitiligo area severity index, changed significantly from 90.1667 to 86.6667 (P = 0.026 ) and on placebo side from 89.6667 to 86.8333 (P = 0.026 ). There was no significant difference between medication and placebo sides in terms of pigmentation (P = 0.566 ). Conclusions . No significant difference in improving repigmentation between medication and placebo sides was seen.